Characterization of MMoO4 (M = Ba, Sr and Ca) with different morphologies prepared using a cyclic microwave radiation - Thongtem T. (2014)
Scheelite molybdates (MMoO4, M = Ba, Sr and Ca) were successfully prepared by the reactions of M(NO3)2·2H2O and Na2MoO4·2H2O in propylene glycol and NaOH using a microwave radiation. The phases were detected using XRD and SAED. TEM analysis revealed the presence of micro-sized bi-pyramids with a square base, nano-sized particles in clusters, and dispersed nano-sized particles for BaMoO4, SrMoO4 and CaMoO4, respectively. Diffraction patterns of the bi-pyramids were simulated, and are in accord with the experimental results. Raman and FTIR spectra provide the evidence of scheelite structure with Mo-O stretching vibration in MoO42- tetrahedrons at 742-901 cm- 1. © 2007 Elsevier B.V. All rights reserved.